2020
DOI: 10.1111/joa.13275
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relationship between the morphology of the styloid process of the ulna and the attachment of the radioulnar ligaments

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…There are reports that the deep and superficial layers of the triangular fibrocartilage complex could not be clearly divided. 7 , 14 Therefore, superficial and deep layers were created for comparison with previous reports. For convenience, the thickness of the RUL was divided in half.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that the deep and superficial layers of the triangular fibrocartilage complex could not be clearly divided. 7 , 14 Therefore, superficial and deep layers were created for comparison with previous reports. For convenience, the thickness of the RUL was divided in half.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the wrist joint from an 80-year-old male cadaver. 7 We decalcified the wrist for 1 week in a solution containing aluminum chloride, hydrochloric acid, and formic acid, as described by Plank and Rychlo. 8 After decalcification, we dehydrated the block with a graded series of ethanols and embedded them in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…3 B). These bony morphological features, particularly cortical bone thickening, are reported to correspond to the high tensile stress from dense connective tissues (Horiuchi et al 2020 ; Tano et al 2021 ). In addition, histological analysis revealed that the ligament-like structure independent of the joint capsule did not exist in the inferior area of the AIIS, and the joint capsule attaches to the inferior area of the AIIS via the fibrocartilage (Fig.…”
Section: Capsular Attachment On the Anterosuperior Acetabular Marginmentioning
confidence: 99%
“…The terminology used in the anatomical studies for this structure showed a large variety with articular disc (proper) ( n = 9) (Benjamin et al, 1990; Chidgey et al, 1991; Ekenstam & Hagert, 1985; Ishii et al, 1998; Kleinman & Graham, 1998; Ohmori & Azuma, 1998; Rein et al, 2015; Semisch et al, 2016; Shigemitsu et al, 2007), disc/disk proper ( n = 6) (Horiuchi et al, 2020; Nakamura et al, 1996; Nakamura et al, 2001; Nakamura & Makita, 2000; Nakamura & Yabe, 2000; Saka et al, 2021), triangular fibrocartilage ( n = 4) (Bednar et al, 1991; Mikic, 1978; Viegas & Ballantyne, 1987; Zhan, Li, et al, 2017), or central disk ( n = 1) (Totterman & Miller, 1995). One study referred to the ulnar attachment fibers of the disc with the term “triangular ligament” (Zhan, Li, et al, 2017).…”
Section: Tfcc Componentsmentioning
confidence: 99%
“…The terminology used for the ligaments showed some variety with the most commonly used terms being: (distal) dorsal and volar/palmar radioulnar ligaments ( n = 8) (Chidgey et al, 1991; Ekenstam & Hagert, 1985; Ishii et al, 1998; Kleinman & Graham, 1998; Rein et al, 2015; Semisch et al, 2016; Totterman & Miller, 1995; Zhan, Li, et al, 2017), (distal) radioulnar ligaments ( n = 8) (Benjamin et al, 1990; Horiuchi et al, 2020; Maniglio et al, 2020; Nakamura et al, 2001; Nakamura & Yabe, 2000; Saka et al, 2021; Shigemitsu et al, 2007; Shin et al, 2017), triangular ligament ( n = 1) (Nakamura et al, 1996) or proximal ligamentous complex ( n = 1) (Nakamura & Makita, 2000). The origin was defined by some studies at the radial attachment and the insertion at the ulnar attachment (Chidgey et al, 1991; Ekenstam & Hagert, 1985; Maniglio et al, 2020; Totterman & Miller, 1995).…”
Section: Tfcc Componentsmentioning
confidence: 99%